Aktualne wyzwania w pracy wychowawczej z młodzieżą gimnazjalną = Current challenges in educational work with middle school youth - Szczęsna, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article concerns current challenges in educational work with youth from middle schools. Educational challenges on the global level and those related to changes in our country are enumerated in the first part. The second part is the analysis of teachers` opinions on the subject of current challenges connected with working with youth. The article ends with a reflection on the teacher`s role in the alternating reality.
Keywords: gimnazjaliści; wychowanie; młodzież gimnazjalna; wyzwania edukacyjne